Opportunities and Benefits of Publishing Tutorial Articles in Scientific Journals - Tanko Titus Auta; Wiwin Martiningsih; Suparji Suparji (Aloha International Journal of Multidisciplinary Advancement (AIJMU), 2021)
EDITORIAL Apart from being a journal that can publish scientific articles from all disciplines of science and technology, Aloha International Journal of Multidisciplinary Advancement (AIJMU) also opens opportunities for authors to publish scientific papers in various forms, both research and non-research articles; what is important is scientific and beneficial to the scientific community. One segment of the scientific community that is in dire need of important information from journals is diploma and undergraduate students. They really need basic level sciences, which can help them to complete their studies. Therefore, AIJMU invited lecturers and researchers to publish articles in tutorial form. The tutorial material is expected to be a new technique or procedure which is a scientific finding that needs to be introduced to the scientific community immediately, but it is also possible to publish other types of tutorials that are considered useful for the scientific community. As an article that is a practical guide, of course, it is likely that the size of the article is relatively long, so especially for tutorial articles, the number of words allowed is not limited, but it is hoped that the author uses a concise and simple presentation style. It is hoped that the tutorial articles published in this journal can really help practitioners, academics and students, who in turn can contribute to the development of science and technology in all disciplines of science and technology.